Addressing the Health Needs of Underserved Populations Through Public Contribution: Prioritisation and Development of a Peer Support Intervention for Sexual and Gender Minority Forced Migrants - Tommy Carlsson; Rogers Kissiti; Maria Jirwe; Elisabet Mattsson; Louise vonEssen; Maria Gottvall (Health Expectations, 2025)
ABSTRACT Introduction The health of underserved populations, including sexual and gender minority forced migrants, is a pressing global concern. Public contribution in research has the potential to enhance prioritisation and aid in intervention development, but has been criticised due to a lack of sufficient diversity and engagement with underserved populations. Methods The core research team conducted eight workshops together with eight experts by lived experience to prioritise and guide future peer support intervention research. Activities included brainstorming, pathway mappings, ranking procedures, storytelling exercises, photovoice sessions and individual open‐ended writing sessions. Open‐ended reflective meetings and manifest content analysis of material, as well as documentation, guided the progress towards final results. Results Peer support was identified as an intervention with the potential to reduce mental health burdens, enhance the capacity to integrate into society and provide access to basic needs. Peer support interventions aiming to reduce health inequities by promoting language proficiency and employment attainment were identified as prioritised areas. A range of considerations and barriers regarding the modality of interventions, the training of peer supporters and recruitment strategies needs further examination in research. Conclusions Our findings illustrate the importance of public contribution when planning research addressing support for underserved and marginalised populations. Public contribution efforts targeting underserved populations such as ours will help researchers gain an in‐depth understanding of prioritised research questions and pragmatic study procedures. In regard to research for sexual and gender minority forced migrants, we recommend prioritisation of intervention development that promotes mental health and reduces loneliness through support from peers in group settings and from peer mentors, informational support and capacity‐building. Patient or Public Contribution Representatives acting as experts by lived experience contributed as research partners throughout the procedures and workshops.